Palladium-catalysed cyclisations of bromoenynamides in the synthesis and applications of amidodienes - Greenaway, R (2013)
The aim of this work was to investigate palladium-catalysed cyclisations of bromoenynamides in the synthesis of amidodienes, which on further reaction or oxidation can lead to a diverse range of heteroaromatic systems. Building upon work within the Anderson group on the palladium-catalysed cyclisations of bromoenynes, we have been able to successfully apply a palladium-catalysed carbopalladation/Stille coupling/electrocyclisation cascade to bromoenynamides and then further develop this to incorporate a Suzuki coupling, leading to bicyclic amidodienes which can undergo selective oxidation to a range of heteroaromatics including indolines, indoles, tetrahydroquinolines and benzazepines. During the investigations into the cascade cyclisation, a reductive cyclisation was discovered which enabled access to a range of monocyclic amidodienes. These could subsequently be subjected to a series of Diels-Alder cycloadditions (thermal, Lewis acid-catalysed, arynes) and oxidations to afford a complimentary range of heteroaromatic systems. Whilst this methodology was successful with bromoenynamides, extension of its application to bromoenynhydrazides, with the hope of accessing a relatively unusual range of heteroaromatic structures including indazoles, cinnolines and diazepines, proved to be more problematic. Finally, expansion of the cascade methodology into a fully intramolecular cyclisation, enabled studies towards the synthesis of the trikentrin family of natural products to be conducted.